Gesture counteracts gender stereotypes conveyed through subtle linguistic cues - Yihan Qian; Susan Goldin-Meadow; Lin Bian (Proceedings of the National Academy of Sciences, 2025)
Despite increased attempts to express equality in speech, biases often leak out through subtle linguistic cues. For example, the subject–complement statement (SCS, “Girls are as good as boys at math”) is used to advocate for equality but often reinforces gender stereotypes (boys are the standard against which girls are judged). We ask whether stereotypes conveyed by SCS can be counteracted by gesture. Two preregistered studies with 8- to 11-y-old children ( N = 320 total) investigate whether an equal gesture—two palms placed at the same height—mitigates the gender stereotype induced by SCS. Children who saw the equal gesture along with SCS were more likely to express egalitarian beliefs than children who saw no gesture or an unequal gesture. Children can extract meaning from gesture when making stereotypical inferences, suggesting that the equal gesture may prove to be an innovative, and simple, intervention to counteract stereotypes introduced by subtle language.